Credit flow to Indian agriculture: Trends and contributing factors - Sahoo, Gagan Bihari; Rajasekhar, D. (Bangalore, 2002)
The credit flow to agriculture, especially to small landholders, has declined during the period 1981 to 1998 at the all-India level, while the total volume of net bank credit increased after the introduction of banking sector reforms in 1991. An analysis of factors influencing the flow of agricultural credit reveal hat banks prefer to deploy their funds for non-agricultural activities earning higher interest income. The credit deposit ratio and the proportion of rural and semi-urban bank branches are positively related to the credit flow to agriculture.
Keywords: Agriculture; Credit